The Economics of Uniqueness : Investing in Historic City Cores and Cultural Heritage Assets for Sustainable Development - Licciardi, Guido; Amirtahmasebi, Rana (Washington, DC: World Bank, 2013)
With rapid urbanization, cities featuring valuable historic cores and heritage assets struggle to modernize without completely losing their uniqueness. The good news is that there is an increasing trend toward financing projects aimed at conserving and incorporating heritage into development strategies. This book presents approaches to balance conservation and development. There are many interesting papers surrounding the topic, but policy and decision makers do not have any easy-to-digest compendium to guide them on how to decide when an element of conservation is warranted, and how much it is worth spending on it. This book presents approaches to combine investment on landmarks and on their surrounding areas, with investment to create jobs and prosperity for local communities, many of them poor, while also contributing to sustainable urbanization and inclusive growth.